1973
DOI: 10.1021/ja00787a040
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical transformations of small ring heterocyclic compounds. XLVII. Electronic details of the photocycloaddition of arylazirines

Abstract: Photoaddition of 2-(/3-Naphthyl)azirine with Acrylonitrile. Irradiation of a mixture of 2-(fi-naphthyl)azirine and acrylonitrile in benzene for 4 hr using a Pyrex filter gave 2-(d-naphthyl)-4-cyano-A'-pyrroline (37) as a crystalline solid (76%). This material was purified by thick layer chromatography using a mixture of 1:1 hexane-ethyl acetate as the eluent and was sublimed at 140°(0.01 mm) to afford an analytical sample, mp 143-144°; ir (KBr) 4.45,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
3

Year Published

1974
1974
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 0 publications
1
33
0
3
Order By: Relevance
“…This procedure has been widely used in the synthesis of a variety of five-membered heterocycles (cf., Scheme 1). [5][6][7][24][25][26][27] Recent quantum-chemical calculations shed some light on the above-mentioned observations. On the basis of complete active space self-consistent field (CASSCF) calculations, Klessinger and Borneman 28,29 demonstrated that the photochemical formation of the nitrile ylide from the respective 2H-azirine (by C-C bond cleavage) occurs in an nπ* singlet excited state and involves a barrierless conical intersection between the S 1 and S 0 potential energy surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has been widely used in the synthesis of a variety of five-membered heterocycles (cf., Scheme 1). [5][6][7][24][25][26][27] Recent quantum-chemical calculations shed some light on the above-mentioned observations. On the basis of complete active space self-consistent field (CASSCF) calculations, Klessinger and Borneman 28,29 demonstrated that the photochemical formation of the nitrile ylide from the respective 2H-azirine (by C-C bond cleavage) occurs in an nπ* singlet excited state and involves a barrierless conical intersection between the S 1 and S 0 potential energy surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…C, C(3a) und C(8a)); 77,9 ( 8 , C (1) (6), 256 (8), 202 (lo), 198 (14), 197 (16), 189 (6), 183 (7), 141 (9), 128,5 (lo), 127 (12), 77 (15). (25), 274 (28), 261 (14), 145 (43), 104 (26), 77 (22). 76 (15).…”
Section: Experimenteller Teilunclassified
“…Dies ist durch eine Vielzahl von Beispielen (vgl. [7]) und insbesondere durch die relativen Geschwindigkeitskonstanten der I, 3-dipolaren Cycloadditionen von Benzonitrilio-phenylmethanid (2 a) an Olefine mit n-Akzeptorsubstituenten [22] sowie von Benzonitrilio-2-propanid (2 b) rnit der Carbonylgruppe von a-halogenierten Essigsauremethylestern [ 111 belegt worden. Andererseits mussten Substituenten, welche die HOMO-Energie des Nitrilylids erhohen, d. h. Donorsubstituenten des Dipols, die 1,3-dipolare Cycloaddition beschleunigen (vgl.…”
unclassified
“…Der durch Photolyse in benzolischer Losung aus 1-Azido-1-phenyl-propen erzeugte Dipol 2c [lo] lieferte mit dem 7,5fachen Uberschuss an Aceton das Addukt 8 nur in bescheidener Ausbeute (16,5y0). Nach Padwa et al [8] ergibt die Photoaddition von Aceton und 2,3-Diphenyl-2H-azirin (lb) (2 : 1 Benzol/Aceton-Losung ; ca. 480facher Acetoniiberschuss) das korrespondierende 3-Oxazolin in einer Ausbeute von knapp 40%.…”
Section: Bestrahlung Von 3-phenyl-2h-azirinen In Gegenwart Vonunclassified
“…With various ketones benzonitrile-isopropylide (2a) gives cyclo-addition products in very good preparative yields (scheme I ) . and benzonitrile-benzylide (2b) [8] react, however, sluggishly with ketones, smooth cyclo-addition being observed in their case only with Pactivateds ketones (2,2,2-trifluoro-acetophenonc, 1,1,1-trifluoro-2-propanone). With la acetonylacetonc forms the bis-adduct 12.…”
mentioning
confidence: 99%